1999
DOI: 10.1177/0265407599163002
|View full text |Cite
|
Sign up to set email alerts
|

Turning Points in the Development of Blended Families

Abstract: A modified retrospective interview technique (RIT) was employed with members of 53 blended families to determine the types of turning points they reported experiencing and the developmental trajectories of their respective blended family’s first 4 years. Findings revealed 15 primary types of turning points, of which ‘Changes in Household Configuration’, ‘Conflict’, ‘Holidays/Special Events’, ‘Quality Time’ and ‘Family Crisis’ were the most frequent. A cluster analysis revealed five basic trajectories of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 31 publications
11
139
1
2
Order By: Relevance
“…Further, our few participants who identified a complete triad structure were split between those who experienced this structure early on and those for whom this structure emerged later. In general, our findings support those who have adopted a turning-points approach to stepfamily development (Baxter, Braithwaite, & Nicholson, 1999;Braithwaite, Olson, Golish, Soukup, & Turman, 2001), in contrast to a clinical-prescriptive model in which all stepfamilies are envisioned to achieve a state of close and positive bonding with the passage of time: a few stepfamilies appear to move rapidly to a complete triad structure, others appear to move more slowly to that structure, and many do not progress there at all.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, our few participants who identified a complete triad structure were split between those who experienced this structure early on and those for whom this structure emerged later. In general, our findings support those who have adopted a turning-points approach to stepfamily development (Baxter, Braithwaite, & Nicholson, 1999;Braithwaite, Olson, Golish, Soukup, & Turman, 2001), in contrast to a clinical-prescriptive model in which all stepfamilies are envisioned to achieve a state of close and positive bonding with the passage of time: a few stepfamilies appear to move rapidly to a complete triad structure, others appear to move more slowly to that structure, and many do not progress there at all.…”
Section: Discussionsupporting
confidence: 82%
“…The findings in the present study complement existing research that is heavily biased in favor of stepfamilies in their early formative years; for example, Baxter, Braithwaite, and Nicholson (1999) studied stepfamily development over the first four years of stepfamily life. While it is important to study these early years, scholars know much less about interaction in established stepfamilies-those stepfamilies that have progressed beyond the first three to five years it takes to establish stable expectations, norms, and patterns (Hetherington, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…Evidently, stepchildren reported no significant differences in frequencies of conflict with all three adults in the stepfamily system. These results are meaningful, given that conflict-related events represent one of the most important discriminators among different stepfamily developmental pathways (Baxter, Braithwaite, & Nicholson, 1999;Coleman et al, 2001). In fact, Schrodt (2006aSchrodt ( , 2006b) recently found that stepfamily dissension is a key indicator of stepfamily functioning, so much so that it often becomes the foremost characteristic of some stepfamily types as it becomes normative over time.…”
Section: Discussionmentioning
confidence: 67%
“…Based on the approach of previous relational and family communication researchers using this method (e.g., Baxter, Braithwaite, & Nicholson, 1999;Baxter & Bullis, 1986;Olson, 2002), we used the RIT graph to serve as a visual model to display turning points reflecting the "child-free" decisionmaking of the couple. Modeled after extant studies, the RIT graph was composed of a vertical (or y) axis that indicated in percentages (0%-100%) how committed the couple was, at any one turning point, about remaining child-free.…”
Section: Data Collectionmentioning
confidence: 99%